Water treatment plant prototype with ph control modeled on fuzzy logic for removing arsenic using fe(VI) and fe(III) - Paredes Larroca, Fabricio Humberto (2020)
This study proposes a fuzzy control strategy embedded in a Siemens IoT2040 gateway developed for removing inorganic arsenic from synthetic underground water in a treatment plant prototype. The prototype is used to dose a constant flow of Fe(VI) to maintain an oxide-reduction potential to guarantee the oxidation of arsenite into arsenate, while the fuzzy logic embedded in the IoT control manages the addition of Fe(III) to achieve a proper pH adjustment and efficient arsenate removal. The tests used synthetic Bangladesh groundwater enriched with 200 µg/L of arsenite and 200 µg/L of arsenate. The results revealed that the plant prototype yielded an effective treatment of the water. Arsenate was decreased to an average value of 6.66 µg/L and, the arsenite concentration decreased to 1.01 µg/L or less. These values were lower than the limit of 10 µg/L deemed by the World Health Organization as safe for human consumption.